PARADIGMA BARU PENDIDIKAN DAN PEMBELAJARAN SEJARAH DALAM MERDEKA BELAJAR-KAMPUS MERDEKA - Hendra Kurniawan (Jurnal Pendidikan Sejarah Indonesia, 2021)
History education requires a new paradigm as the times and society change. The conventional paradigm is considered no longer to answer the needs of society. In addition to the presence of postmodernism that broke the establishment, people today are also faced with Society 5.0. A new era marked by increasingly rapid technological advances and all practicalities must be addressed so that humans remain at the center of life's arrangement. In facing the dynamics of these changes, history education must strengthen its relevance and role for society. This article aims to examine a new paradigm that can strengthen history education as a vehicle for building individual identities as part of society, nation, and citizens of the world. A change in the paradigm of history education is practically manifested in history learning which includes aspects of teaching materials and the learning process. This change is also closely related to the Merdeka Belajar-Kampus Merdeka program that has been launched. It is hoped that history education with its new paradigm will be more contextual in fostering historical awareness for a more humanist life in the present to look to the future.